Rekonstruksi Sejarah Pemikiran dan Peradaban Islam Era Dinasti Umayyah dalam Pendidikan Islam - Mar'atus Sholihah (STAIFAS-Press, 2019)
This paper is focusing on the development of science in Umayyah Dynasty The Ist Era which is the beginning of Islamic golden age. Umayyah Dynasty was built by Mu‟awiyah Ibn Abu Sufyan and had monarchy system for its government which led by fourteen Khalifa (Leaders). Science had been built in its era by developing libraries in all areas, whether in cities or villages; building the first formal school in primary level; translating greek and roman books into Arabic; and prospering teachers and ulama‟. But, unfortunately this era had to end because of many rea-sons which found by historical proofs. This paper also tries to give some recon-structions to learn from the previous mistakes of Umayyah Dinasty The Ist Era, so that we as moslems do not repeat those mistakes for ourselves and our generations ahead.